Toward Co-productive Learning? The Exchange Network as Experimental Space - Matthews, Rachel; Papoulias, Constantina (Stan) (Frontiers in Sociology, 2019)
Policy around patient and public involvement (PPI) in the production, design and delivery of health services and research remains difficult to implement. Consequently, in the UK and elsewhere, recent years have seen a proliferation of toolkits, training, and guidelines for supporting good practice in PPI. However, such instruments rarely engage with the power asymmetries shaping the terrain of collaboration in research and healthcare provision. Toolkits and standards may tell us little about how different actors can be enabled to reflect on and negotiate such asymmetries, nor on how they may effectively challenge what count as legitimate forms of knowledge and expertise. To understand this, we need to turn our attention to the relational dynamic of collaboration itself. In this paper we present the development of the Exchange Network, an experimental learning space deliberately designed to foreground and work on this relational dynamic in healthcare research and quality improvement. The Network brings together diverse actors (researchers, clinicians, patients, carers and managers) for structured ‘events’ which are not internal to particular research or improvement projects but subsist at a distance from these. Such events thus temporarily suspend the role allocation, structure, targets and other pragmatic constraints of such projects. We discuss how Exchange Network participants make use of action learning techniques to reflect critically on such constraints; how they generate a ‘knowledge space’ in which they can rehearse and test a capacity for dialogue: an encounter between potentially conflictual forms of knowledge. We suggest that Exchange Network events, by explicitly attending to the dynamics and tensions of collaboration, may enable participants to collectively challenge organisational norms and expectations and to seed capacities for learning, as well as generate new forms of mutuality and care.